Climatic conditions, cultural diversity, and labor productivity - Erich Gundlach; Ximena Matus-Velasco (Kiel Institute of World Economics (IfW), 2000)
Countries with the highest labor productivity overwhelmingly lie in the world's temperate climatic zones far away from the equator. The question we address is whether climatic conditions as measured by distance from the equator remain correlated with labor productivity after other variables are taken into account. We find that climatic conditions do not have a significant impact on labor productivity once we control for factor accumulation and cultural diversity within countries. Our regression results suggest that cultural diversity as measured by the degree of ethnolinguistic fractionalization may severely limit economic development in presently poor countries.
Keywords: O4; 330; climatic conditions; factor accumulation; ethnolinguistic diversity; productivity; Arbeitsproduktivität; Klima; Wirtschaftsethnologie; Investition; Bildungsinvestition; Multikulturell; Schätzung; Welt